Comparative analyses of albumin/globulin grain proteome fraction in differentially salt‐tolerant Tunisian barley landraces reveals genotype‐specific and defined abundant proteins. (19th February 2019) - Riahi, J.; Amri, B.; Chibani, F.; Azri, W.; Mejri, S.; Bennani, L.; Zoghlami, N.; Matros, A.; Mock, H. P.; Ghorbel, A.; Jardak, R.
Abstract: Salinity is one of the major abiotic stresses threatening crop production and yield worldwide. Breeding programmes are therefore needed to improve yield under cultivation in soil. Traits from locally adopted landraces provide a resource to assist breeding of novel elite genotypes. Here, we examine differentially expressed proteins by performing comparative proteomic profiling of the albumin/globulin grain fraction of Tunisian barley genotype landraces with contrasting salinity tolerance. Tunisian barley Boulifa (B, tolerant) and Testour (T, sensitive) mature grains were assessed in 2‐DE profiles. Differentially expressed spots, with an abundance enhanced 1.5‐fold in the grain, were subjected to MALDI TOF/TOF MS for identification. Distinctiveness between tolerant and sensitive genotypes was proved in the albumin/globulin fraction using PCA; 64 spots showed significant differential abundance. Increased accumulation of 40 spots was confirmed in Boulifa with, interestingly, four genotype‐specific spots. Two of these four spots were sHSP. Proteins with highest abundance were serpin Z7, 16.9 KDa Class I HSP and phosphogluconolactonase 2. Proteins such as expansin, kiwellin, kinesin and succinyl‐CoA ligase were identified for the first time in barley grain. Moreover, ß‐amylase, LEA family and others were identified as abundant in Boulifa. On the other hand, proteins more accumulated in Testour are implicated mainly in ROS scavenging and protease inhibition. Our results clearly indicate proteomic contrast between the two selected genotypes. With identification of specific HSP, high abundant stress‐protective and other defined proteins, we provide biochemical traits that will support breeding programmes to address the threat of salinity in agricultural production.